Global wind stilling and the role of sub-monthly variability in explaining deficiencies in atmospheric reanalyses - Paul-Arthur Monerie; Reinhard Schiemann; David J. Brayshaw; Jon I. Robson (Climate Dynamics, 2026)
Terrestrial near-surface (10-m) wind speed decreased over the Northern Hemisphere between 1980 and 2010. We revisit this ‘global stilling’ by comparing station-based observations and multiple atmospheric reanalysis products and assessing their ability to capture the past changes in near-surface wind speed. We show, using a station-based wind speed dataset from the Met Office (HadISD3), that global stilling is robust and not an artefact of analysis method or observational network characteristics. In contrast to a previous study, we find that atmospheric reanalyses fail to reproduce the observed changes in wind speed over the Northern Hemisphere land, Europe and China. By decomposing wind speed variability into contributions from sub-monthly and monthly timescales, we show that the error in capturing the global stilling trend is primarily due to trends in the sub-monthly component. The exception are the products from the Japanese Meteorological Agency (JRA55 and JRA55C), which reproduce global stilling over the Northern Hemisphere and Europe with high skill, though this appears to be attributable to correction when producing the dataset rather than being a fundamental property of the forecast systems used to produce the reanalysis. Our results highlight the importance of resolving sub-monthly wind variability in reanalyses and raise critical questions about the drivers of global stilling and the reliability of reanalysis-based prediction systems for understanding past and future variations of the near-surface wind speed.

Key drivers of large scale changes in North Atlantic atmospheric and oceanic circulations and their predictability - Buwen Dong; Yevgeny Aksenov; Ioana Colfescu; Ben Harvey; Joël Hirschi; Simon Josey; Hua Lu; Jenny Mecking; Marilena Oltmanns; Scott Osprey; Jon Robson; Stefanie Rynders; et al. (Climate Dynamics, 2025)
Significant changes have occurred during the last few decades across the North Atlantic climate system, including in the atmosphere, ocean, and cryosphere. These large-scale changes play a vital role in shaping regional climate and extreme weather events across the UK and Western Europe. This review synthesizes the characteristics of observed large-scale changes in North Atlantic atmospheric and oceanic circulations during past decades, identifies the drivers and physical processes responsible for these changes, outlines projected changes due to anthropogenic warming, and discusses the predictability of these circulations. On multi-decadal time scales, internal variability, anthropogenic forcings (especially greenhouse gases), and natural forcings (such as solar variability and volcanic eruptions) are identified as key contributors to large-scale variability in North Atlantic atmospheric and oceanic circulations. However, there remain many uncertainties regarding the detailed characteristics of these various influences, and in some cases their relative importance. We therefore conclude that a better understanding of these drivers, and more accurate quantification of their relative roles, are crucial for more reliable decadal predictions and projections of regional climate for the North Atlantic and Europe.

Large diversity in AMOC internal variability across NEMO-based climate models - Alcide Zhao; Jon Robson; Rowan Sutton; Michael W.K. Lai; Jennifer V. Mecking; Stephen Yeager; Tillys Petit (Climate Dynamics, 2024)
We characterise, and explore the drivers of, differences in the internal variability of the atlantic meridional overturning circulation (AMOC) across five NEMO-based CMIP6 class climate models. While the variability of AMOC variability is dominated by its lower dense limb in all models, there is large diversity in the timescale, multidecadal variability, and latitudinal coherence of AMOC across models. In particular, the UK models have much weaker AMOC multidecadal variability and latitudinal coherence. The model diversity is associated with differences in salinity-governed surface density variations which drive high-density water mass transformation (WMT) in the Greenland–Iceland–Norwegian Seas (GIN) and the Arctic. Specifically, GIN Seas WMT shows large multidecadal variability which has a major impact on AMOC variability in non-UK models. In contrast, the smaller variability in GIN Seas WMT in the UK models has limited impact on the lower latitude AMOC via the Denmark strait overflow mass transport. This leads to a latitudinally less coherent and weaker multidecadal variability of the AMOC lower limb. Such differences between UK and non-UK models are related to differences in model mean states and densification processes in the Arctic and GIN Seas. Consequently, we recommend further in-depth studies to better understand and constrain processes driving salinity changes in the Arctic and GIN Seas for more reliable representation of the AMOC in climate models.

Summer compound heatwaves over China: projected changes at different global warming levels and related physical processes - Mingming Zhang; Buwen Dong; Reinhard Schiemann; Jon Robson (Climate Dynamics, 2024)
Based on the multi-model ensemble mean of CMIP6 simulations, the future changes in frequency, intensity and duration of Compound (both daytime and nighttime) heatwaves (HWs) in summer over China at various global warming levels (GWLs) under the SSP3-7.0 and SSP5-8.5 are assessed. HWs over China become more frequent and hotter, and the duration of HWs becomes longer compared to those in the recent climate. The magnitudes of these changes are primarily dependent on GWLs, but they are not very sensitive to the scenarios. At 4 ℃ GWL, the frequency of HWs increases by more than fivefold under both scenarios, and the intensity (duration) of HWs averaged under the two scenarios is 2.28 ℃ hotter (3.59 days longer) than the one in the recent climate over the entire China. Meanwhile, the maximum duration of HW events can reach more than 25 days in summer in comparison with 8 days in the recent climate. The changes in HW properties are regionally dependent at the four GWLs. For example, the largest increase in HW frequency is over the Northwest China, the largest increase in intensity in HWs is seen over the Northeast and Northwest, and the largest increase in HW duration is over the Southwest China. The extreme rare events (50-year and 100-year events) in the recent climate would become the norm over China and four sub-regions at 4 ℃ GWL. Overall, seasonal mean warming dominates the changes in HW properties over China at the different GWLs. The seasonal mean warming in summer across China is related to the increases of longwave radiation, partly due to increase in greenhouse gas forcing and partly resulted from increased water vapor and the increase of shortwave radiation (under the SSP5-8.5) over eastern China related to decreases in aerosols and total cloud cover. Furthermore, the regional variations in the water vapor over China are consistent with atmospheric circulation changes. The seasonal mean surface warming results in enhanced upward sensible and latent heat fluxes, leading to increased summer mean daily maximum and minimum of near-surface air temperature and the enhancement of HWs properties over the entire China. Changes of shortwave radiation tend to play a weaker role for surface warming under the SSP3-7.0 than those under the SSP5-8.5, which is related to increased aerosol changes under the SSP3-7.0.

Correction to: Coupled climate response to Atlantic Multidecadal Variability in a multi-model multi-resolution ensemble - Daniel L. R. Hodson; Pierre-Antoine Bretonnière; Christophe Cassou; Paolo Davini; Nicholas P. Klingaman; Katja Lohmann; Jorge Lopez-Parages; Marta Martín-Rey; Marie-Pierre Moine; Paul-Arthur Monerie; Dian A. Putrasahan; Christopher D. Roberts; et al. (Climate Dynamics, 2023)

Coupled climate response to Atlantic Multidecadal Variability in a multi-model multi-resolution ensemble - Daniel L. R. Hodson; Pierre-Antoine Bretonnière; Christophe Cassou; Paolo Davini; Nicholas P. Klingaman; Katja Lohmann; Jorge Lopez-Parages; Marta Martín-Rey; Marie-Pierre Moine; Paul-Arthur Monerie; Dian A. Putrasahan; Christopher D. Roberts; et al. (Climate Dynamics, 2022)
North Atlantic sea surface temperatures (SSTs) underwent pronounced multidecadal variability during the twentieth and early twenty-first century. We examine the impacts of this Atlantic Multidecadal Variability (AMV), also referred to as the Atlantic Multidecadal Oscillation (AMO), on climate in an ensemble of five coupled climate models at both low and high spatial resolution. We use a SST nudging scheme specified by the Coupled Model Intercomparision Project’s Decadal Climate Prediction Project Component C (CMIP6 DCPP-C) to impose a persistent positive/negative phase of the AMV in the North Atlantic in coupled model simulations; SSTs are free to evolve outside this region. The large-scale seasonal mean response to the positive AMV involves widespread warming over Eurasia and the Americas, with a pattern of cooling over the Pacific Ocean similar to the Pacific Decadal Oscillation (PDO), together with a northward displacement of the inter-tropical convergence zone (ITCZ). The accompanying changes in global atmospheric circulation lead to widespread changes in precipitation. We use Analysis of Variance (ANOVA) to demonstrate that this large-scale climate response is accompanied by significant differences between models in how they respond to the common AMV forcing, particularly in the tropics. These differences may arise from variations in North Atlantic air-sea heat fluxes between models despite a common North Atlantic SST forcing pattern. We cannot detect a widespread effect of increased model horizontal resolution in this climate response, with the exception of the ITCZ, which shifts further northwards in the positive phase of the AMV in the higher resolution configurations.

Role of the Atlantic multidecadal variability in modulating East Asian climate - Paul-Arthur Monerie; Jon Robson; Buwen Dong; Dan Hodson (Climate Dynamics, 2021)
We assess the effects of the North Atlantic Ocean Sea Surface Temperature (NASST) on North East Asian (NEA) surface temperature. We use a set of sensitivity experiments, performed with MetUM-GOML2, an atmospheric general circulation model coupled to a multi-level ocean mixed layer model, to mimic warming and cooling over the North Atlantic Ocean. Results show that a warming of the NASST is associated with a significant warming over NEA. Two mechanisms are pointed out to explain the NASST—North East Asia surface temperature relationship. First, the warming of the NASST is associated with a modulation of the northern hemisphere circulation, due to the propagation of a Rossby wave (i.e. the circumglobal teleconnection). The change in the atmosphere circulation is associated with advections of heat from the Pacific Ocean to NEA and with an increase in net surface shortwave radiation over NEA, both acting to increase NEA surface temperature. Second, the warming of the NASST is associated with a cooling (warming) over the eastern (western) Pacific Ocean, which modulates the circulation over the western Pacific Ocean and NEA. Additional simulations, in which Pacific Ocean sea surface temperatures are kept constant, show that the modulation of the circumglobal teleconnection is key to explaining impacts of the NASST on NEA surface temperature.

A Blueprint for an Inclusive, Global Deep-Sea Ocean Decade Field Program - Kerry L. Howell; Ana Hilário; A. Louise Allcock; David M. Bailey; Maria Baker; Malcolm R. Clark; Ana Colaço; Jon Copley; Erik E. Cordes; Roberto Danovaro; Awantha Dissanayake; Elva Escobar; et al. (Frontiers in Marine Science, 2020)
The ocean plays a crucial role in the functioning of the Earth System and in the provision of vital goods and services. The United Nations (UN) declared 2021–2030 as the UN Decade of Ocean Science for Sustainable Development. The Roadmap for the Ocean Decade aims to achieve six critical societal outcomes (SOs) by 2030, through the pursuit of four objectives (Os). It specifically recognizes the scarcity of biological data for deep-sea biomes, and challenges the global scientific community to conduct research to advance understanding of deep-sea ecosystems to inform sustainable management. In this paper, we map four key scientific questions identified by the academic community to the Ocean Decade SOs: (i) What is the diversity of life in the deep ocean? (ii) How are populations and habitats connected? (iii) What is the role of living organisms in ecosystem function and service provision? and (iv) How do species, communities, and ecosystems respond to disturbance? We then consider the design of a global-scale program to address these questions by reviewing key drivers of ecological pattern and process. We recommend using the following criteria to stratify a global survey design: biogeographic region, depth, horizontal distance, substrate type, high and low climate hazard, fished/unfished, near/far from sources of pollution, licensed/protected from industry activities. We consider both spatial and temporal surveys, and emphasize new biological data collection that prioritizes southern and polar latitudes, deeper (> 2000 m) depths, and midwater environments. We provide guidance on observational, experimental, and monitoring needs for different benthic and pelagic ecosystems. We then review recent efforts to standardize biological data and specimen collection and archiving, making “sampling design to knowledge application” recommendations in the context of a new global program. We also review and comment on needs, and recommend actions, to develop capacity in deep-sea research; and the role of inclusivity - from accessing indigenous and local knowledge to the sharing of technologies - as part of such a global program. We discuss the concept of a new global deep-sea biological research program ‘ Challenger 150 ,’ highlighting what it could deliver for the Ocean Decade and UN Sustainable Development Goal 14.

Can the boundary profiles at 26° N be used to extract buoyancy-forced Atlantic Meridional Overturning Circulation signals? - Irene Polo; Keith Haines; Jon Robson; Christopher Thomas (Ocean Science, 2020)
The temporal variability of the Atlantic Meridional Overturning Circulation (AMOC) is driven both by direct wind stresses and by the buoyancy-driven formation of North Atlantic Deep Water over the Labrador Sea and Nordic Seas. In many models, low-frequency density variability down the western boundary of the Atlantic basin is linked to changes in the buoyancy forcing over the Atlantic subpolar gyre (SPG) region, and this is found to explain part of the geostrophic AMOC variability at 26∘ N. In this study, using different experiments with an ocean general circulation model (OGCM), we develop statistical methods to identify characteristic vertical density profiles at 26∘ N at the western and eastern boundaries, which relate to the buoyancy-forced AMOC. We show that density anomalies due to anomalous buoyancy forcing over the SPG propagate equatorward along the western Atlantic boundary (through 26∘ N), eastward along the Equator, and then poleward up the eastern Atlantic boundary. The timing of the density anomalies appearing at the western and eastern boundaries at 26∘ N reveals ∼ 2–3-year lags between boundaries along deeper levels (2600–3000 m). Record lengths of more than 26 years are required at the western boundary (WB) to allow the buoyancy-forced signals to appear as the dominant empirical orthogonal function (EOF) mode. Results suggest that the depth structure of the signals and the lagged covariances between the boundaries at 26∘ N may both provide useful information for detecting propagating signals of high-latitude origin in more complex models and potentially in the observational RAPID (Rapid Climate Change programme) array. However, time filtering may be needed, together with the continuation of the RAPID programme, in order to extend the time period.

Processes shaping the spatial pattern and seasonality of the surface air temperature response to anthropogenic forcing - Fangxing Tian; Buwen Dong; Jon Robson; Rowan Sutton; Laura Wilcox (Climate Dynamics, 2020)
In the period 1960–2010, the land surface air temperature (SAT) warmed more rapidly over some regions relative to the global mean. Using a set of time-slice experiments, we highlight how different physical processes shape the regional pattern of SAT warming. The results indicate an essential role of anthropogenic forcing in regional SAT changes from the 1970s to 2000s, and show that both surface–atmosphere interactions and large-scale atmospheric circulation changes can shape regional responses to forcing. Single forcing experiments show that an increase in greenhouse gases can lead to regional changes in land surface warming in winter (DJF) due to snow-albedo feedbacks, and in summer (JJA) due to soil-moisture and cloud feedbacks. Changes in anthropogenic aerosol and precursor (AA) emissions induce large spatial variations in SAT, characterized by warming over western Europe, Eurasia, and Alaska. In western Europe, SAT warming is stronger in JJA than in DJF due to substantial increases in clear sky shortwave radiation over Europe, associated with decreases in local AA emissions since the 1980s. In Alaska, the amplified SAT warming in DJF is due to increased downward longwave radiation, which is related to increased water vapor and cloud cover. In this case, although the model was able to capture the regional pattern of SAT change, and the associated local processes, it did not simulate all processes and anomalies correctly. For the Alaskan warming, the model is seen to achieve the correct regional response in the context of a wider North Pacific anomaly that is not consistent with observations. This demonstrates the importance of model evaluation that goes beyond the target variable in detection and attribution studies.

Predicting the seasonal evolution of southern African summer precipitation in the DePreSys3 prediction system - Paul-Arthur Monerie; Jon Robson; Buwen Dong; Bastien Dieppois; Benjamin Pohl; Nick Dunstone (Climate Dynamics, 2019)

Forced decadal changes in the East Asian summer monsoon: the roles of greenhouse gases and anthropogenic aerosols - Fangxing Tian; Buwen Dong; Jon Robson; Rowan Sutton (Climate Dynamics, 2018)

Recent multivariate changes in the North Atlantic climate system, with a focus on 2005–2016 - Jon Robson; Rowan T. Sutton; Alex Archibald; Fenwick Cooper; Matthew Christensen; Lesley J. Gray; N. Penny Holliday; Claire Macintosh; Malcolm McMillan; Ben Moat; Maria Russo; Rachel Tilling; et al. (International Journal of Climatology, 2018)
Major changes are occurring across the North Atlantic climate system, including in the atmosphere, ocean and cryosphere, and many observed changes are unprecedented in instrumental records. As the changes in the North Atlantic directly affect the climate and air quality of the surrounding continents, it is important to fully understand how and why the changes are taking place, not least to predict how the region will change in the future. To this end, this article characterizes the recent observed changes in the North Atlantic region, especially in the period 2005–2016, across many different aspects of the system including: atmospheric circulation; atmospheric composition; clouds and aerosols; ocean circulation and properties; and the cryosphere. Recent changes include: an increase in the speed of the North Atlantic jet stream in winter; a southward shift in the North Atlantic jet stream in summer, associated with a weakening summer North Atlantic Oscillation; increases in ozone and methane; increases in net absorbed radiation in the mid‐latitude western Atlantic, linked to an increase in the abundance of high level clouds and a reduction in low level clouds; cooling of sea surface temperatures in the North Atlantic subpolar gyre, concomitant with increases in the western subtropical gyre, and a decline in the Atlantic Ocean's overturning circulation; a decline in Atlantic sector Arctic sea ice and rapid melting of the Greenland Ice Sheet. There are many interactions between these changes, but these interactions are poorly understood. This article concludes by highlighting some of the key outstanding questions.

A role of the Atlantic Ocean in predicting summer surface air temperature over North East Asia? - Paul-Arthur Monerie; Jon Robson; Buwen Dong; Nick Dunstone (Climate Dynamics, 2018)

Decadal prediction of the North Atlantic subpolar gyre in the HiGEM high-resolution climate model - Jon Robson; Irene Polo; Dan L. R. Hodson; David P. Stevens; Len C. Shaffrey (Climate Dynamics, 2018)

Mechanisms of decadal variability in the Labrador Sea and the wider North Atlantic in a high-resolution climate model - Pablo Ortega; Jon Robson; Rowan T. Sutton; Martin B. Andrews (Climate Dynamics, 2017)

Decadal predictions of the cooling and freshening of the North Atlantic in the 1960s and the role of ocean circulation - Jon Robson; Rowan Sutton; Doug Smith (Climate Dynamics, 2014)

Evaluating the potential for statistical decadal predictions of sea surface temperatures with a perfect model approach - Ed Hawkins; Jon Robson; Rowan Sutton; Doug Smith; Noel Keenlyside (Climate Dynamics, 2011)